(untitled) (Biological Sciences - PJSIR, 2000)
The raingun (pY,-30) with 6 mm diameter nozzle was operated under different pressures ranging from 20 to 80 psi. The discharge of the raingun and the radius of coverage increased with the increase in pressure being 12.59 gpm and 18.:5m at 80 psi pressure. The maximum and minimum theoretical application rates were found to be 2.66 mm h" at 80 psi and 1.33 mm h’ at 35 psi, respectively. In respect of coverage the high coefficients of uniformity were found in the first quarter and the low coefficients of uniformity in the fourth quarter.